2020
DOI: 10.1177/0091647120926488
|View full text |Cite
|
Sign up to set email alerts
|

Changes after an Educational Intervention to Teach about and Promote Forgiveness among Seminarians and Practicing Clergy

Abstract: Many studies of forgiveness have found that relatively short psychosocial interventions aimed at promoting forgiveness can result in noticeable increases in participants’ decisional and emotional forgiveness in their day-to-day lives. However, most of those interventions involve engagement in short psychoeducational experiential activities and participants want to forgive something. Less is known about a purely educational forgiveness intervention’s effects on participants’ subsequent knowledge and self-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Awareness-raising guidelines have been offered online (https://www.evworthington-forgiveness.com). Worthington et al (2020) reported on a program to train pastors in better preaching, especially preaching about forgiveness consistent with what the research shows to be true about forgiveness. After a week of instruction, the participants had more accurate knowledge of forgiveness, had more confidence in their knowledge, and had forgiven more than at the outset of the program.…”
Section: Changing Religious Communitiessupporting
confidence: 78%
See 1 more Smart Citation
“…Awareness-raising guidelines have been offered online (https://www.evworthington-forgiveness.com). Worthington et al (2020) reported on a program to train pastors in better preaching, especially preaching about forgiveness consistent with what the research shows to be true about forgiveness. After a week of instruction, the participants had more accurate knowledge of forgiveness, had more confidence in their knowledge, and had forgiven more than at the outset of the program.…”
Section: Changing Religious Communitiessupporting
confidence: 78%
“…Clinicians could assist clergy by training and supervising lay group leaders, consulting with pastors, or conducting groups (either pro bono or for pay by the church). In addition, Worthington et al (2020) found a positive effect on clergy knowledge and confidence by providing workshops for clergy. Practitioners could organize workshops in the community for clergy or even conduct large-scale workshops for laypeople from numerous local churches.…”
Section: Recommendation For Collaborating With Clergymentioning
confidence: 94%
“…Ten questions from a four-option multiple-choice Forgiveness Knowledge Test [18] assessed comprehension of ten statements concerning forgiveness (e.g., "Holding onto a sense of injustice has negative effects on . .…”
Section: Forgivenessmentioning
confidence: 99%